2014
DOI: 10.24198/jkp.v2n3.2
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang berhubungan Toilet Trainingpada Anak Prasekolah

Abstract: AbstrakAnak bukan dewasa kecil, anak menunjukkan ciri-ciri pertumbuhan dan perkembangan sesuai dengan usianya. Toilet training perlu dilakukan selama anak berada dalam periode optimal untuk menghindari efek jangka panjang seperti inkontinensia dan infeksi saluran kemih (ISK). Anak yang terbiasa memakai diaper sejak kecil akan mengalami keterlambatan dalam toilet training. Tujuan penelitian ini untuk mengidentifikasi faktor-faktor yang berhubungan dengan keberhasilan toilet training pada anak usia 4-5 tahun (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Separation from family, death of parents, birth of siblings, new environment, fights of parents, or child abuse is a condition that is most often considered as a contributing factor to enuresis [2], [6], [13]. In a study in Semarang about the relationship between stress and enuresis, it was found that 61.7% of children who had experienced psychological disorders experienced enuresis [6], [14]. The results of the analysis of the two variables indicate that there was a significant relationship between the poor child's psychological factors for the incidence of enuresis.…”
Section: Resultsmentioning
confidence: 99%
“…Separation from family, death of parents, birth of siblings, new environment, fights of parents, or child abuse is a condition that is most often considered as a contributing factor to enuresis [2], [6], [13]. In a study in Semarang about the relationship between stress and enuresis, it was found that 61.7% of children who had experienced psychological disorders experienced enuresis [6], [14]. The results of the analysis of the two variables indicate that there was a significant relationship between the poor child's psychological factors for the incidence of enuresis.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini sejalan dengan peneli an yang dilakukan oleh Andriani (2014), bahwa terdapat hubungan yang signifikan antara pengetahuan ibu dengan pelaksanaan toilet training, bahwa ibu yang berpengetahuan lebih cenderung dak melaksanakan toilet training pada anak usia prasekolah di Poliklinik Anak Rumah Sakit TK. II Dus ra Cimahi.…”
Section: Hubungan Pengetahuan Ibu Dengan Pelaksanaan Toilet Trainingunclassified
“…Berdasarkan pendapat Hidayat (2005) yang mengu p hasil peneli an Andriani, dkk (2014) la han BAB atau BAK pada anak sangat membutuhkan persiapan bagi ibu, baik secara fisik, psikologis, maupun intelektual. Melalui persiapan tersebut, anak diharapkan dapat mengontrol kemampuan BAB atau BAK secara mandiri.…”
unclassified
See 1 more Smart Citation